Student engagement and perceived gains in transnational education in Ghana. Issue 4 (6th April 2021) - Owusu-Agyeman, Yaw; Amoakohene, Gertrude
Abstract : Purpose: Following recent calls for partner institutions to address the seeming weaknesses in transnational education (TNE) delivery especially in host institutions, this article was developed to generate new insights into how student engagement could explain perceived gains in TNE in a host university in Ghana. Design/methodology/approach: A quantitative research design was used to gather and analyse data from students ( n  = 197) who were enrolled in different masters' programmes with three different TNE partners from Europe. We relied on a survey to collect data from participants who were sampled by way of simple random sampling method. Consequently, the data was analysed using structural equation modelling. Findings: Results revealed that the psychological, behavioural and sociocultural perspectives of student engagement have positive effect on students' perceived gains in TNE. Across the findings, student–lecturer engagement, student' assessment, students' sense of belonging and peer engagement demonstrated strong positive effect on students' perceived gains in TNE. The study further revealed that a supportive campus environment and cross-cultural interaction among students enhance students' sense of belonging. Originality/value: The findings of this article add to an emerging body of literature that suggest that student engagement provides rich information for enhancing the experiences of students who enrol in TNE programmes. Additionally, by integrating supportive campus environment as part of the multidimensional construct which has not been addressed in previous TNE student engagement literature, this shows the significance of institutional structures and commitment to supporting student engagement.